Penerapan Pembelajaran Kooperatif dengan Berbagai Model - Miftahun Najwa Gazali; Revi Ramadani; Gusmaneli Gusmaneli (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study discusses cooperative learning models as an approach that emphasizes collaboration among students to achieve optimal learning outcomes. The main focus is on three types of cooperative models: Jigsaw, Student Teams Achievement Division (STAD), and Teams Games Tournament (TGT). The background of this study is the need for active, participatory, and collaborative learning methods to improve students’ understanding of the material. The purpose of the study is to describe the steps and characteristics of each model. The method used is a literature review from various relevant academic sources. The results show that each model has its own advantages in promoting active student engagement, enhancing individual and group responsibility, and strengthening understanding through teamwork. The Jigsaw model is effective in fostering positive interdependence among students, STAD encourages academic competition within teams, and TGT creates a fun learning environment through games. In conclusion, cooperative learning models can serve as a strategic alternative for creating meaningful, student-centered learning experiences.